Compositions, methods of making compositions
Patent Information
- Application Number
- CN202580019071.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-09-10
- Filing Date
- 2025-03-03
- Publication Date
- 2026-10-16
AI Technical Summary
[0003]然而,银等金属作为芯片贴装材料过硬,并且Si、SiC等半导体元件与银等金属层之间的热膨胀系数差非常大,因此在超过200℃的热疲劳试验中,会在烧结部发生裂纹的扩展、或者导致上述半导体元件、DBC(Direct Bonded Copper,直接敷铜)等绝缘基板发生破裂等,在耐热性方面不充分
[0033] When used for sintering bonding, the compositions disclosed herein can achieve sintering at low temperatures and can bond strongly, forming sintered bodies with excellent heat resistance.
Smart Images

Figure CN122935461A_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to compositions and methods of manufacturing the compositions. This application claims priority to Japanese Patent Application No. 2024-34444, filed on March 6, 2024, and Japanese Patent Application No. 2024-157033, filed on September 10, 2024, the contents of which are incorporated herein by reference. Background Technology
[0002] In recent years, sintering bonding as described below has been studied: In chip bonding (chip mounting) of semiconductor devices such as SiC chips that operate at high temperatures, a metal paste containing nano-sized or micro-sized particles of silver and copper is used as the bonding material. This bonding material is sandwiched between the components to be bonded and heated for a given time, causing the silver and other metals in the bonding material to sinter, thereby bonding the components to each other through a metal bonding layer (e.g., Patent Document 1). This metal bonding technology is highly anticipated for various applications in electronic components such as power semiconductor devices and LED devices.
[0003] However, metals such as silver are too rigid as chip mounting materials, and the difference in thermal expansion coefficients between semiconductor devices such as Si and SiC and the metal layers such as silver is very large. Therefore, in thermal fatigue tests exceeding 200°C, cracks may propagate in the sintered area, or the aforementioned semiconductor devices and insulating substrates such as DBC (Direct Bonded Copper) may crack, indicating insufficient heat resistance. In addition, if the bonding material is a metallic element, there is no other way to improve the bonding strength and heat resistance except by controlling the density of sintering, which means that the mechanical properties of the bond cannot be fundamentally changed.
[0004] To address the aforementioned issues, materials that combine low-temperature processability and heat resistance are known to be obtained by supporting specific metal nanoparticles on a carrier (e.g., Patent Document 2).
[0005] Existing technical documents
[0006] Patent documents
[0007] Patent Document 1: International Publication No. 2018 / 037992
[0008] Patent Document 2: Japanese Patent Application Publication No. 2010-65265 Summary of the Invention
[0009] The problem that the invention aims to solve
[0010] However, the combination of known metal nanoparticles with elemental substances has limitations, and the functions they can perform are also limited. Therefore, materials with better low-temperature sintering properties and heat resistance are desired.
[0011] Therefore, the object of this disclosure is to provide a composition that, when used for sintering bonding, not only enables sintering at low temperatures but also provides strong bonding and forms a sintered body with excellent heat resistance.
[0012] Problem Solving Methods
[0013] In order to solve the above-mentioned problems, the inventors of this disclosure conducted in-depth research and discovered that if a composition containing composite particles and satisfying specific physical property values during sintering is used, sintering can be achieved at low temperatures, and a strong bond can be formed to create a sintered body with excellent heat resistance. The composite particles include substrate particles and Ag and / or Cu supported on the substrate particles, and the substrate particles satisfy specific physical properties. The invention of this disclosure is based on these insights.
[0014] That is, the purpose of this disclosure is to provide a composition comprising composite particles, organic matter, and particles containing Ag and / or Cu other than the composite particles, wherein the composite particles comprise substrate particles and Ag and / or Cu supported on the substrate particles, the linear expansion coefficient of the substrate particles is 8 ppm / K or less, and the particle sintering rate of the composition expressed by the following formula (1) is 30% or more.
[0015] Particle sintering rate = (Total number of substrate particles with a length of 100 nm or more oriented in at least one direction and bonded to the bonded material in an image obtained by taking a cross-section of the sintered body after the following sintering process at 20,000x magnification using FE-SEM) / (Total number of substrate particles with a length of 100 nm or more oriented in at least one direction in an image obtained by taking a cross-section of the sintered body after the following sintering process at 20,000x magnification using FE-SEM) (1)
[0016] Sintering process: The above composition is printed on a Cu substrate with a 2μm thick Ag coating using a metal mask (5mm opening, 0.15mm mask thickness). The Cu substrate is placed on a heating plate maintained at 100°C and held for 1 minute. Then it is removed from the heating plate and allowed to return to room temperature. The Cu substrate is then placed on a heating plate maintained at 250°C and held for 30 minutes. Then it is removed from the heating plate and allowed to return to room temperature.
[0017] By incorporating a specific combination of composite particles, metal particles, and organic matter into the above composition, and by achieving a sintering rate of 30% or more for the aforementioned particles, sintering can be achieved at low temperatures, resulting in a strong bond and the formation of a sintered body with excellent heat resistance.
[0018] In the above composition, the substrate particles are preferably particles selected from Si, W, SiO2, Cr and Mo.
[0019] Preferably, the volume ratio of Ag and / or Cu in all particles contained in the above composition is 50 to 95%.
[0020] Preferably, the average number of the following particle aggregates A in the image obtained by taking pictures of any 5 parts of the cross section of the above-mentioned composite particles at 1000x magnification using SEM is 2 or less.
[0021] Particle aggregate A: contains multiple substrate particles, and Ag and / or Cu, wherein the area ratio of the supported Ag and / or Cu is more than 70% relative to the substrate particles, and the diameter of the longest part of the aggregate is more than 5 μm.
[0022] In addition, this disclosure provides a method for manufacturing a composition comprising a solvent and composite particles on which a metal is supported. The manufacturing method includes a step of irradiating a composition (A) comprising the substrate particles, a metal compound that is a raw material for the metal, and a solvent with ultrasound in order to manufacture the composite particles. The manufacturing method yields a composition with a particle sintering rate of 30% or more as expressed by the following formula (1).
[0023] Particle sintering rate = (Total number of substrate particles with a length of 100 nm or more oriented in at least one direction and bonded to the bonded material in an image obtained by taking a cross-section of the sintered body after the following sintering process at 20,000x magnification using FE-SEM) / (Total number of substrate particles with a length of 100 nm or more oriented in at least one direction in an image obtained by taking a cross-section of the sintered body after the following sintering process at 20,000x magnification using FE-SEM) (1)
[0024] Sintering process: The above composition is printed on a Cu substrate with a 2μm thick Ag coating using a metal mask (5mm opening, 0.15mm mask thickness). The Cu substrate is placed on a heating plate maintained at 100°C and held for 1 minute. Then it is removed from the heating plate and allowed to return to room temperature. The Cu substrate is then placed on a heating plate maintained at 250°C and held for 30 minutes. Then it is removed from the heating plate and allowed to return to room temperature.
[0025] In the above-mentioned process of irradiating ultrasound, the temperature of the above-mentioned composition (A) is preferably 20~100°C.
[0026] In the above-mentioned process of irradiating with ultrasound, the preferred irradiation conditions are a frequency of 5~1000kHz and an output of 10~1000W.
[0027] Preferably, the solvent in the above composition comprises water or an alcohol.
[0028] Preferably, the above composition (A) further comprises a reducing agent.
[0029] Preferably, the above composition (A) further comprises a carboxylic acid.
[0030] Preferably, the substrate particles are particles selected from Si, W, SiO2, Cr and Mo.
[0031] Preferably, the metal compounds are metal oxides and / or metal carboxylates.
[0032] The effects of the invention
[0033] When used for sintering bonding, the compositions disclosed herein can achieve sintering at low temperatures and can bond strongly, forming sintered bodies with excellent heat resistance. Attached Figure Description
[0034] Figure 1 This is an FE-SEM image obtained by photographing a cross-section of a sintered body of a composition according to one embodiment of the present disclosure.
[0035] Figure 2 The image is a FE-SEM image obtained by photographing the cross-section of the sintered body of Example 1.
[0036] Figure 3 The image is an FE-SEM image obtained by photographing the cross-section of the sintered body of Example 2.
[0037] Figure 4 The image is a FE-SEM image obtained by photographing the cross-section of the sintered body of Comparative Example 1.
[0038] Symbol Explanation
[0039] 1: Composite particles
[0040] 2: The object to be joined
[0041] 21: Particles other than composite particles
[0042] 22: Substrate
[0043] 23, 24, 25: Silver flakes
[0044] 3: Silicon particles Detailed Implementation
[0045] [Composition]
[0046] By including composite particles, organic matter, and particles containing Ag and / or Cu other than the aforementioned composite particles in the composition disclosed herein, wherein the composite particles include substrate particles and Ag and / or Cu supported on the substrate particles, the linear expansion coefficient of the substrate particles is 8 ppm / K or less, and the particle sintering rate of the composition expressed by the following formula (1) is 30% or more, thereby enabling sintering at low temperatures and strong bonding when used for sintering bonding, and forming a sintered body with excellent heat resistance.
[0047] Particle sintering rate = (Total number of substrate particles with a length of 100 nm or more oriented in at least one direction and bonded to the bonded material in an image obtained by taking a cross-section of the sintered body after the following sintering process at 20,000x magnification using FE-SEM) / (Total number of substrate particles with a length of 100 nm or more oriented in at least one direction in an image obtained by taking a cross-section of the sintered body after the following sintering process at 20,000x magnification using FE-SEM) (1)
[0048] Sintering process: The above composition is printed on a Cu substrate with a 2μm thick Ag coating using a metal mask (5mm opening, 0.15mm mask thickness). The Cu substrate is placed on a heating plate maintained at 100°C and held for 1 minute. Then it is removed from the heating plate and allowed to return to room temperature. The Cu substrate is then placed on a heating plate maintained at 250°C and held for 30 minutes. Then it is removed from the heating plate and allowed to return to room temperature.
[0049] It should be noted that the bonded material in formula (1) above includes substances that the composite particles can bond to. Specifically, in addition to the composite particles contained in the above composition, other particles besides the composite particles, and the above composition, it also includes substrates, electronic components, etc. Furthermore, "composite particles bonded to the bonded material" refers to composite particles bonded to at least one of the bonded materials mentioned above.
[0050] Figure 1 The image is an FE-SEM image obtained by photographing the sintered body of the above composition. It can be confirmed that the sintered composite particles 1 are bonded together with the bonded materials 2, such as particles 21 other than the composite particles and substrate 22.
[0051] Of all the particles contained in the above composition, the volume ratio of Ag and / or Cu is preferably 50-95% by volume, more preferably 60-95% by volume, and even more preferably 70-90% by volume. It should be noted that the particles that can be contained in the above composition include the above-described composite particles, particles containing Ag and / or Cu other than the above-described composite particles, and particles other than the above-described particles.
[0052] The particle sintering rate of the above composition is 30% or more, preferably 35% or more, and more preferably 37% or more. By making the particle sintering rate 30% or more, it is possible to bond strongly to the substrate. Furthermore, as an upper limit, there is no particular limitation, and it can be 100%.
[0053] Furthermore, the unit sintering ratio represented by the following formula (2) of the above composition is preferably 0.7 or more, more preferably 1.0 or more, further preferably 2.0 or more, and particularly preferably 3 or more. By making the unit sintering ratio 0.7 or more, bonding can be performed more effectively during sintering.
[0054] Unit sintering rate = (particle sintering rate) / (the ratio of the volume of Ag and / or Cu supported to the volume of the substrate particles) (2)
[0055] It should be noted that when the volume of the substrate particles in the composite particles is set as VA and the volume ratio of the supported Ag and / or Cu is set as VB, the ratio of the volume of the supported Ag and / or Cu to the volume of the substrate particles is specifically expressed by the following formula (3).
[0056] (The ratio of the volume of Ag and / or Cu carried to the volume of the substrate particles) = VB / (VA + VB) (3)
[0057] Alternatively, volume can be represented by the respective area in the image captured by SEM.
[0058] Furthermore, there are no particular limitations on the form of the above-mentioned composition; examples include pastes and inks.
[0059] (composite particles)
[0060] The aforementioned composite particles comprise the aforementioned substrate particles and Ag and / or Cu supported on the aforementioned substrate particles. The aforementioned substrate particles comprise particles selected from one or more raw materials chosen from Si, W, SiO2, Cr, and Mo. The aforementioned Ag and / or Cu are preferably uniformly supported on the aforementioned substrate particles in the form of Ag particles and / or Cu particles, or they can be supported on the aforementioned substrate particles in a film-like manner by increasing the adhesion amount. It should be noted that, in the case of film-like support, it can be a film of elemental Ag or Cu, or a film containing both Ag and Cu. It should be noted that in the above composition, only one type of composite particle can be used, or two or more types can be used.
[0061] In the image obtained by taking a picture of the above-mentioned composite particles using SEM at 1000x magnification, the number of particle agglomerates A is preferably 2 or less, more preferably 1 or less, and even more preferably there are no particle agglomerates A. By making the number of particle agglomerates A 2 or less, not only is heat resistance easily achieved, but it also means that Ag or Cu is not unevenly present in the composite particles, and Ag and / or Cu are uniformly supported on the substrate particles, thereby resulting in excellent sinterability.
[0062] Particle aggregate A: contains multiple substrate particles, and Ag and / or Cu, wherein the area ratio of the supported Ag and / or Cu is more than 70% relative to the substrate particles, and the diameter of the longest part of the aggregate is more than 5 μm.
[0063] The number of substrate particles contained in the aforementioned particle agglomerate A is preferably 30% or less, more preferably 15% or less, further preferably 5% or less, particularly preferably 3% or less, and most preferably there is no particle agglomerate A. By ensuring that the total number of substrate particles contained in the aforementioned particle agglomerate A is 30% or less, the amount of Ag and / or Cu in the composite particles can be moderate, and heat resistance can be easily achieved.
[0064] The quantity of the aforementioned particle agglomerates A, the quantity of substrate particles contained in the aforementioned particle agglomerates A, and the quantity of the aforementioned substrate particles can be counted by embedding the composite particles of this disclosure in epoxy resin and allowing it to cure, based on images obtained by taking cross-sectional images using SEM. It should be noted that the quantity of substrate particles also includes the quantity of substrate particles contained in the aforementioned particle agglomerates A. Furthermore, the evaluation of the quantity of the aforementioned particle agglomerates A and the quantity of the aforementioned substrate particles represents the average value taken from any five locations in the aforementioned sample.
[0065] Furthermore, in the image obtained by taking a picture of the composite particles at 1000x magnification using SEM, the number of particle agglomerates B is preferably 2 or less, more preferably 1 or less, and even more preferably there are no particle agglomerates B. By making the number of particle agglomerates B 2 or less, not only is heat resistance easily achieved, but it also means that Ag or Cu is not unevenly present in the composite particles, and Ag and / or Cu are uniformly supported on the substrate particles, thereby resulting in excellent sinterability.
[0066] Particle aggregate B: Contains multiple substrate particles, and Ag and / or Cu, wherein the area ratio of the supported Ag and / or Cu is more than 70% relative to the substrate particles, the porosity in the particle aggregate is less than 30% and the diameter of the longest part of the aggregate is more than 5 μm.
[0067] The amount of substrate particles contained in the aforementioned particle agglomerate B is preferably 30% or less, more preferably 15% or less, further preferably 5% or less, particularly preferably 3% or less, and most preferably there is no particle agglomerate B. By making the amount of substrate particles contained in the aforementioned particle agglomerate B 30% or less, the amount of Ag and / or Cu in the composite particles can be made appropriate, and heat resistance can be easily achieved.
[0068] The quantity of the aforementioned particle agglomerate B, the quantity of substrate particles contained in the aforementioned particle agglomerate B, and the quantity of substrate particles can also be determined by the same method as for the aforementioned particle agglomerate A.
[0069] When Ag is supported in particle form, the content of Ag in 100% by mass is preferably 95% by mass or more, more preferably 99% by mass or more, and can be 99.9% by mass or more, or 100% by mass. That is, it can be elemental Ag particles. In addition to Ag, other components may include silver oxide as a raw material, silver carboxylate as a reaction intermediate, protective agents, and other additives, but from the viewpoint of improving sinterability, it is preferable not to include the aforementioned components other than Ag. It should be noted that when Ag is supported in an elemental film form, the same range as described above is also preferable.
[0070] Similarly, when Cu is supported in particle form, the proportion of Cu in 100% by mass of the Cu particles is preferably 95% by mass or more, more preferably 99% by mass or more, and can be 99.9% by mass or more, or 100% by mass. That is, it can be elemental Cu particles. In addition to Cu, other components may include copper oxide as a raw material, copper carboxylate as a reaction intermediate, protective agents, and other additives, but from the viewpoint of improving sinterability, it is preferable not to include the aforementioned components other than Cu. It should be noted that when Cu is supported in a film-like form as elemental Cu, it is also preferable to satisfy the same range as described above.
[0071] The average particle size (median particle size) of the Ag and Cu particles described above is preferably 10,000 nm or less, more preferably 1,000 nm or less, even more preferably 500 nm or less, particularly preferably 200 nm or less, particularly preferably 100 nm or less, and particularly preferably 50 nm or less. As a lower limit, there is no particular limitation, but from a manufacturing point of view, it is preferably 1 nm or more, more preferably 5 nm or more, and even more preferably 10 nm or more. It should be noted that the above average particle size (median particle size) is calculated based on the particle volume and can be measured by laser diffraction / scattering.
[0072] When the Ag and / or Cu described above are supported in a film form on the substrate particles, the thickness is preferably 10 nm to 10 μm, more preferably 50 nm to 5 μm, and even more preferably 100 nm to 3 μm. By making the thickness 10 nm or more, bonding can be easily performed during sintering. In addition, by making it 10 μm or less, low-temperature sintering properties are easily achieved.
[0073] From the viewpoint of reducing the coefficient of thermal expansion of the composite particles and improving heat resistance, when Ag is supported, Si and / or SiO2 particles are preferred as the substrate particles; when Cu is supported, particles selected from W, Cr, and Mo are preferred as the substrate particles. However, when Si is used as the substrate particle and Ag is supported, from the viewpoint of reducing particle agglomerates A, composite particles not manufactured by physical processing such as ball milling are preferred. It should be noted that only one type or more types of substrate particles may be used.
[0074] Furthermore, the aforementioned substrate particles may also contain components other than those exemplified above. To facilitate the support of Ag and Cu, the total content (100% by mass) of Si, SiO2, W, Cr, and Mo in the substrate particles is preferably 90% by mass or more, more preferably 95% by mass or more, further preferably 99% by mass or more, particularly preferably 99.9% by mass or more, and may also be 100% by mass. It should be noted that if SiO2, W, Cr, and Mo contain components that are not present, the total content of these components preferably satisfies the above-mentioned range.
[0075] The average particle size (median particle size) of the aforementioned substrate particles is preferably 0.05 to 50 μm, more preferably 0.1 to 30 μm, and even more preferably 0.5 to 10 μm. By making the average particle size 0.05 μm or more, the surface area of the element becomes appropriate, making it easier for metal particles to be supported on the surface. Furthermore, by making it 50 μm or less, heat resistance is easily achieved during sintering. It should be noted that the aforementioned average particle size (median particle size) is calculated based on particle volume and can be measured using laser diffraction / scattering methods.
[0076] The shape of the aforementioned substrate particles is not particularly limited; for example, spherical, sheet-like (flat), or polyhedral shapes are possible.
[0077] The volume ratio of the substrate particles to Ag and / or Cu in the composite particles of this disclosure [substrate particles: Ag and / or Cu] is preferably 99.9:0.1 to 50:50, more preferably 99:1 to 80:20, and even more preferably 99.5:0.5 to 90:10. Even if the volume ratio of Ag and / or Cu to the substrate particles is within the above range, the composite particles of this disclosure can be strongly bonded, and therefore can be effectively sintered.
[0078] The linear expansion coefficient of the aforementioned substrate particles is 8 ppm / K or less, more preferably 7 ppm / K or less, and even more preferably 6 ppm / K or less. By setting the linear expansion coefficient to 8 ppm / K or less, heat resistance is easily achieved. Furthermore, as a lower limit, there is no particular limitation, and it can be 1 ppm / K or more. It should be noted that the aforementioned coefficient of thermal expansion can be measured, for example, using a thermomechanical analysis apparatus (apparatus name "TMA-60", manufactured by Shimadzu Corporation).
[0079] (Methods for manufacturing composite particles)
[0080] The aforementioned composite particles can be manufactured using a manufacturing method that includes the following steps: irradiating a composition (A) containing the aforementioned substrate particles, a metal compound that is a raw material for the aforementioned metal, and a solvent with ultrasound. It should be noted that, in this disclosure, the composition used to manufacture the composite particles is sometimes referred to as "composition (A)".
[0081] The aforementioned metal can be supported on the aforementioned substrate particles in a particle form, or it can be supported on the aforementioned substrate particles in a film form by increasing the amount of adhesion.
[0082] The metals mentioned above are preferably Ag and / or Cu, and the substrate particles are preferably selected from one or more raw materials chosen from Si, W, SiO2, Cr, and Mo. Furthermore, when the metal is Ag, the substrate particles are preferably particles made from Si and / or SiO2; when the metal is Cu, the substrate particles are preferably particles selected from W, Cr, and Mo. It should be noted that the Ag, Cu, and substrate particles mentioned above are preferably the same as those described in the composite particles section.
[0083] The preferred temperature for irradiating the composition with ultrasound is 20-100°C, more preferably 25-90°C, and even more preferably 30-80°C. It should be noted that the temperature of the composition can be appropriately varied within the above range through specific process steps. Furthermore, ultrasonic treatment instantaneously generates tiny bubbles called cavitations, which repeatedly undergo quasi-adiabatic expansion and compression, eventually collapsing. During this process, the cavitation bubbles themselves become extremely hot / high pressure, generating shock waves and jets upon collapse. Therefore, in the method for manufacturing composite particles disclosed herein, even when the temperature of the composition is maintained at a relatively low level within the above range, the reduction reaction of the aforementioned metal compound can occur.
[0084] As for the irradiation conditions when irradiating the aforementioned ultrasonic waves, the frequency is preferably in the range of 5 to 1000 kHz, more preferably 20 to 200 kHz. Furthermore, although the output and irradiation time are affected by capacity and temperature, the output is preferably 10 to 1000 W, more preferably 20 to 300 W. In addition, the irradiation time is preferably in the range of 0.5 to 50 hours.
[0085] In addition to the ultrasonic irradiation step, the aforementioned method for manufacturing composite particles may also include an irradiation heat step. Examples of irradiation heat methods include those using lasers or microwaves. Specifically, the laser can be generated using an excimer laser or a YAG laser, and the microwave can be generated using a microwave generator with a frequency of 2.45 GHz and an output of approximately 50 to 1500 W. It should be noted that the irradiation heat step can be performed before the ultrasonic treatment step, but from the viewpoint of effectively forming composite particles, it is preferable to perform the irradiation heat step after the ultrasonic treatment step.
[0086] Examples of solvents mentioned above include water and organic solvents. Examples of organic solvents include reducing organic solvents and non-reducing organic solvents. Examples of reducing organic solvents include alcohols such as ethanol, methanol, 2-propanol, and 2-ethylhexanol; aldehydes such as acetaldehyde; and polyols such as glycols. Examples of non-reducing organic solvents include toluene, hexane, cyclohexane, xylene, and benzene. Among these, water and alcohols are preferred, and water, ethanol, methanol, and 2-propanol are more preferred. It should be noted that only one solvent or two or more solvents may be used.
[0087] To fully utilize the effect of ultrasonic treatment, the viscosity of the solvent is preferably 10 mPa·s or less. However, there is no particular limitation on the lower limit, and it can be 0.1 mPa·s or more.
[0088] The aforementioned metal compounds are components that form the raw materials for Ag and Cu in the aforementioned composite particles. There are no particular limitations on the metal compounds as long as they contain either Ag or Cu; specific examples include metal oxides such as silver oxide and copper oxide, and metal carboxylates such as silver acetate and copper acetate. It should be noted that only one type of metal compound may be used, or two or more may be used.
[0089] In addition, the aforementioned metal compounds may include compounds that are added directly as raw materials, as well as compounds generated as reaction intermediates.
[0090] The content of the aforementioned metal compound is preferably 0.05 to 10% by mass, more preferably 0.1 to 5% by mass, relative to 100% of the total amount of the composition. By keeping the amount of metal compound added within the above range, metal particles can be easily formed on the surface of the substrate particles.
[0091] In addition, the above composition may also contain other components besides the substrate particles, the metal compound, and the solvent. Examples of such other components include additives such as protective agents and reducing agents.
[0092] Examples of protective agents include those coating the surfaces of Ag and Cu. These protective agents can be compounds having lone pairs of electrons and functional groups capable of coordinative adsorption of Ag and Cu. In particular, compounds having functional groups containing nitrogen atoms are preferred because they can coordinatively adsorb onto metal surfaces. Examples of nitrogen-containing functional groups include amine groups and imide groups. It should be noted that only one type of protective agent or two or more types can be used.
[0093] Examples of such protective agents include primary amine compounds such as ethylamine and dodecylamine, secondary amine compounds such as dimethylamine and diethylamine, tertiary amine compounds such as triethylamine, and polymers containing functional groups such as ethyl polyvinylpyrrolidone.
[0094] The content of the protective agent is preferably 1 to 10% by mass, more preferably 2 to 5% by mass, relative to 100% of the total composition. By keeping the amount of protective agent added within the above range, the amount added relative to Ag and Cu can be made sufficient.
[0095] The reducing agent described above is a component added to facilitate the reduction of metal compounds by ultrasonic treatment, thereby forming Ag and Cu on the substrate particles. One or more reducing agents may be used.
[0096] Examples of reducing agents include lithium aluminum hydride, sodium thiosulfate, hydrogen peroxide, hydrogen sulfide, borane, diborane, hydrazine, potassium iodide, citric acid, oxalic acid, ascorbic acid, and other carboxylic acids. Among these, carboxylic acids and hydrazine are preferred.
[0097] The content of the reducing agent is preferably 1 to 10% by mass, more preferably 2 to 7% by mass, relative to 100% of the total amount of the composition. By keeping the amount of the protective agent within the above range, Ag and Cu can be easily generated from the metal compound.
[0098] After synthesizing the composite particles using the above method, they are separated and purified using known or conventional methods, thereby producing composite particles. Composite particles produced in this way are highly safe and can be manufactured at low temperatures because they use only low-toxicity raw materials. Furthermore, by using ultrasonic treatment, a high-energy environment can be locally created, thus inducing decomposition and reduction reactions at the metal compounds while simultaneously causing Ag and / or Cu to precipitate on the surface of the substrate particles, producing composite particles with a high density of Ag and / or Cu on the surface of the substrate particles.
[0099] Furthermore, when attempting to physically load Ag and / or Cu onto the surface of substrate particles using methods such as ball milling, excessive Ag and / or Cu can easily be loaded, resulting in the aforementioned particle agglomerates, which can negatively impact heat resistance. On the other hand, the aforementioned composite particle manufacturing method allows for the loading of appropriate amounts of Ag and / or Cu onto the surface of substrate particles by precipitating Ag and / or Cu, thus easily achieving superior heat resistance.
[0100] (Particles containing Ag and / or Cu other than the composite particles mentioned above)
[0101] In addition, the above composition contains particles containing Ag and / or Cu other than the composite particles described above. Among these, Ag particles or Cu particles are preferred as other particles because they can strongly bond with the Ag or Cu supported on the substrate particles in the composite particles. In particular, Ag particles are preferred when the composite particles are supported on Ag, and Cu particles are preferred when they are supported on Cu.
[0102] The volume average particle size (median particle size) of the other particles mentioned above is preferably 0.1 to 100 μm, more preferably 0.3 to 50 μm, and even more preferably 0.5 to 10 μm. By making the volume average particle size 0.1 μm or more, processing becomes easier. By making it 100 μm or less, bonding reliability is easily achieved.
[0103] The shape of the other particles mentioned above is not particularly limited. Examples include spherical, sheet-like (flat), and polyhedral shapes. Particles of the same shape can be used alone, or particles of different shapes can be used in combination. Among these, spherical shapes are preferred for the reason that they can be properly dispersed in the alloy paste.
[0104] The content of the other particles is preferably 5 to 2000 parts by mass, more preferably 10 to 1000 parts by mass, and even more preferably 20 to 500 parts by mass, and particularly preferably 40 to 400 parts by mass, relative to 100 parts by mass of the composite particles. By making the content of the other particles 5 parts by mass or more, they can be fully bonded with the composite particles during sintering, and by making it 2000 parts by mass or less, the coefficient of linear expansion is easily reduced.
[0105] (Organic matter)
[0106] The above composition contains an organic compound. Examples of such organic compounds include: reducing organic compounds, basic compounds, coordinating organic compounds other than those belonging to the category of basic compounds, resins, organic solvents, etc. Only one type of organic compound may be used, or two or more may be used.
[0107] <Reduced organic compounds>
[0108] Examples of reducing organic compounds include, but are not limited to, substances listed below as organic solvents. Examples include: alcohols (lower alcohols such as ethanol, higher alcohols such as palmitol), aldehydes (formaldehyde, acetaldehyde, cyclic trimers and tetramers of these aldehydes), amino acids, organic acids (carboxylic acids, etc.), and aromatic compounds (polyphenols, phenolic acid compounds, etc.). From the viewpoint of exhibiting acidity, organic acids (carboxylic acids, etc.) and aromatic compounds are preferred; from the viewpoint of being easily handled at room temperature and having low toxicity, carboxylic acids are more preferred. Only one of these compounds may be used, or two or more may be used.
[0109] Examples of the aforementioned carboxylic acids include formic acid, acetic acid, lactic acid, propionic acid, acrylic acid, malic acid, hexanoic acid, succinic acid, octanoic acid, tartaric acid, oxalic acid, and malonic acid. Among these, formic acid, oxalic acid, and malonic acid are preferred from the viewpoint of easily obtaining sintered bodies with excellent reducing properties and excellent electrical conductivity.
[0110] From the viewpoint of excellent reducing properties and superior void suppression, the aforementioned reducing organic compound preferably contains formic acid or malonic acid. Furthermore, from the viewpoint of being able to exert reducing properties over a wide temperature range, the aforementioned reducing organic compound preferably contains, in addition to formic acid, a compound with a boiling point higher than formic acid (especially a compound with a boiling point higher than that of a coordination organic compound).
[0111] When formic acid is included as a reducing organic compound, the content of formic acid relative to the total amount of the reducing organic compound (100% by mass) is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 80% by mass or more. Furthermore, when formic acid is included along with other reducing organic compounds (e.g., compounds with boiling points higher than formic acid), the content of the other reducing organic compounds relative to 1 mole of formic acid is preferably 0.1 moles or less, more preferably 0.05 moles or less.
[0112] Relative to the total amount (100% by mass) of the above composition, the content of the reducing organic compound is preferably 5% by mass or less (e.g., 0.1 to 5% by mass), more preferably 0.1 to 4.0% by mass, further preferably 0.2 to 3.7% by mass, and particularly preferably 0.3 to 3.5% by mass.
[0113] <Alkaline compounds>
[0114] As for the aforementioned alkaline compound, there is no particular limitation as long as it can function as a base and achieve the effects of the present invention. Specific examples include nitrogen-containing compounds such as ammonia, amine compounds, phosphine, and phosphorus-containing compounds such as phosphate esters. From the viewpoint of easily obtaining a sintered body with excellent electrical conductivity, nitrogen-containing compounds represented by the following formula (1) are preferred.
[0115] [Chemical Formula 1]
[0116] In equation (1), R a ~R c "Same or different" refers to a hydrogen atom or a hydrocarbon group that may have substituents. "Same or different" also refers to a substituent selected from at least one group chosen from amino, N-substituted amino, N,N-substituted amino, imino, N-substituted imino, and hydroxyl. Wherein, R... a ~R c They are not both hydrogen atoms. The double lines containing dashed lines indicate either a single or double bond; in the case of a double bond, R is absent. c R a ~R c Any two atoms in the atom can also bond together with each other and form a ring with the adjacent nitrogen atom.
[0117] As R a ~R c The hydrocarbon group can be an aliphatic hydrocarbon group, an alicyclic hydrocarbon group, or an aromatic hydrocarbon group, among which aliphatic hydrocarbon groups and alicyclic hydrocarbon groups are preferred, and aliphatic hydrocarbon groups are more preferred.
[0118] Examples of aliphatic hydrocarbon groups include straight-chain or branched alkyl groups, straight-chain or branched alkenyl groups, straight-chain or branched alkynyl groups, and straight-chain or branched alkyl groups, with straight-chain or branched alkyl groups being preferred.
[0119] The linear or branched alkyl group is preferably a linear alkyl group with 1 to 20 carbon atoms, more preferably a linear alkyl group with 1 to 15 carbon atoms, or preferably a branched alkyl group with 3 to 12 carbon atoms, more preferably a linear alkyl group with 3 to 8 carbon atoms, and even more preferably a branched alkyl group with 3 to 6 carbon atoms. Examples include: methyl, ethyl, propyl, butyl, pentyl, hexyl, decyl, dodecyl, tetradecyl, octadecyl, isopropyl, isobutyl, sec-butyl, tert-butyl, 2-ethylhexyl, etc.
[0120] The linear or branched alkenyl group is preferably a linear alkenyl group with 2 to 12 carbon atoms, more preferably 2 to 8 carbon atoms, and even more preferably 2 to 4 carbon atoms. Alternatively, it is preferably a branched alkenyl group with 3 to 12 carbon atoms, more preferably 3 to 8 carbon atoms, and even more preferably 3 to 6 carbon atoms. Examples include: vinyl, 1-propenyl, 2-propenyl, 1-butenyl, 2-butenyl, 3-butenyl, 1-pentenyl, 2-pentenyl, 3-pentenyl, 4-pentenyl, 1-hexenyl, 3-hexenyl, 5-hexenyl, 1-heptenyl, 1-octenyl, 1-nonenyl, 1-decenyl, isopropenyl, 2-methyl-1-propenyl, methallyl, 3-methyl-2-butenyl, 4-methyl-3-pentenyl, etc.
[0121] The linear or branched alkynyl group is preferably a linear alkynyl group with 2 to 12 carbon atoms, more preferably 2 to 8 carbon atoms, and even more preferably 2 to 4 carbon atoms. Alternatively, it is preferably a branched alkynyl group with 3 to 12 carbon atoms, more preferably 3 to 8 carbon atoms, and even more preferably 3 to 6 carbon atoms. Examples include: ethynyl, 1-propynyl, 2-propynyl, 1-butynyl, 2-butynyl, 3-butynyl, 1-pentynyl, 2-pentynyl, 3-pentynyl, 4-pentynyl, 1-hexynyl, 2-hexynyl, 3-hexynyl, 4-hexynyl, 5-hexynyl, 1-hepynyl, 1-octyynyl, 1-nonynyl, 1-decynyl, trimethylsilylethynyl, triethylsilylethynyl, etc.
[0122] The linear or branched alkane chain is preferably a linear alkane chain with 1 to 12 carbon atoms, more preferably 1 to 8 carbon atoms, and even more preferably 2 to 4 carbon atoms. Alternatively, it is preferably a branched alkane chain with 3 to 12 carbon atoms, more preferably 3 to 8 carbon atoms, and even more preferably 3 to 6 carbon atoms. Examples include: methyl alkane, propylene alkane, isopropylene alkane, butyl alkane, isobutyl alkane, sec-butyl alkane, pentyl alkane, isopentyl alkane, octyl alkane, isooctyl alkane, etc.
[0123] Examples of alicyclic hydrocarbon groups include cycloalkyl and cycloalkenyl groups.
[0124] The cycloalkyl group is preferably a cycloalkyl group with 3 to 12 carbon atoms, more preferably a cycloalkyl group with 4 to 10 carbon atoms, and even more preferably a cycloalkyl group with 5 to 8 carbon atoms. Examples include cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl, cyclodecyl, etc.
[0125] The cycloalkenyl group is preferably a cycloalkenyl group with 3 to 12 carbon atoms, more preferably a cycloalkenyl group with 4 to 10 carbon atoms, and even more preferably a cycloalkenyl group with 5 to 8 carbon atoms, for example: cyclopentenyl, cyclohexenyl, etc.
[0126] As an aromatic hydrocarbon group, it is preferably an aryl group with 6 to 18 carbon atoms, more preferably with 6 to 14 carbon atoms, and even more preferably with 6 to 10 carbon atoms, such as phenyl, naphthyl, etc.
[0127] In equation (1), the double lines containing dashed lines represent single or double bonds. When the double lines containing dashed lines represent double bonds, R does not exist. c R in equation (1) a and R b The bonded nitrogen atom represents an imino or an N-substituted imino.
[0128] R a ~R c The total number of amino groups, N-substituted amino groups, and N,N-substituted amino groups that may be present is preferably 0 to 6, more preferably 1 to 4, and even more preferably 1 to 2.
[0129] R a ~R c The total number of imino groups and N-substituted imino groups that may be present is preferably 0 to 4, more preferably 1 to 3, and even more preferably 1 to 2.
[0130] R a ~R c The total number of hydroxyl groups that may be present is preferably 0 to 6, more preferably 1 to 4, and even more preferably 1 to 2.
[0131] The substituents of the above-mentioned N-substituted amino, N,N-substituted amino, and N-substituted imino groups are the same as those of the above-mentioned R. a ~R c The hydrocarbon groups involved are the same.
[0132] R a ~R c Any two atoms in the ring can bond together with each other and form a ring together with the adjacent nitrogen atom. Examples of the rings that can be formed include: pyrrolidine ring, pyrrololine ring, piperidine ring, pyrrole ring, imidazoline ring, imidazoline ring, piperazine ring, imidazoline ring, pyridine ring, diazine ring, triazine ring, etc.
[0133] R a ~R c The hydrocarbon group involved can have substituents other than amino, N-substituted amino, N,N-substituted amino, imino, N-substituted imino, or hydroxyl. Examples of such substituents include: halogen atoms (fluorine, chlorine, bromine, iodine), oxo groups, substituted oxygen groups (alkoxy groups with 1 to 4 carbon atoms, aryl groups with 6 to 10 carbon atoms, aryloxy groups with 6 to 10 carbon atoms, arylalkoxy groups with 7 to 16 carbon atoms, acyloxy groups with 1 to 4 carbon atoms, etc.), carboxyl groups, substituted oxygen carbonyl groups (alkoxy carbonyl groups with 1 to 4 carbon atoms, aryloxy carbonyl groups with 6 to 10 carbon atoms, arylalkoxy carbonyl groups with 7 to 16 carbon atoms, etc.), cyano, nitro, sulfono, mercapto, heterocyclic groups, etc.
[0134] As a specific example of a basic compound represented by formula (1), one could cite, for example, R in formula (1). a ~R c At least one of them is a linear or branched alkylamine; R in formula (1) a R b Independently composed of hydrogen atoms or straight-chain or branched alkyl groups, R c It is a monoalkyl alcohol amine with a straight-chain or branched alkyl group having one hydroxyl group; R in formula (1) a It is a hydrogen atom or a straight-chain or branched alkyl group, R b and R c Dialkylamines that are the same or different from linear or branched alkyl groups having a hydroxyl group; R in formula (1) a ~R c The same or different are trialkylolamines with a straight-chain or branched alkyl group having a hydroxyl group; R in formula (1) a R b The same or different are hydrogen atoms, straight-chain or branched alkyl groups, R c It is an aminoalkane diol with two hydroxyl groups, either linear or branched alkyl groups; R in formula (1) a ~R c It is a diamine having a total of 1 amino group; R in formula (1) a ~R c It is a triamine having a total of 2 amino groups; R in formula (1) a ~R c It is a diaminoalkanol having a total of 1 amino group and a total of 1 hydroxyl group; R in formula (1) a ~R c An imidazole compound containing a total of 1 imino group and forming a ring by containing the nitrogen atom of the imino group; R in formula (1) a Rb Nitrogen-containing aromatic compounds (pyridine compounds, diazine compounds, triazine compounds, etc.) whose bonded nitrogen atom is an imino group and which contains the imino group to form a ring.
[0135] Examples of the aforementioned alkylamines include: methylamine, ethylamine, propylamine, butylamine, pentanamine, dimethylamine, diethylamine, dipropylamine, dibutylamine, dipentanamine, piperidine, trimethylamine, triethylamine, dimethyldecylamine, dimethyldodecylamine, 4-dimethylaminopyridine, 2-aminopyrazine, 2-aminopyrimidine, 3-aminopyridazine, 2-aminotriazine, diazabicyclononene, diazabicycloundecene, etc.
[0136] Examples of the aforementioned monoalkanolamines include: 2-aminoethanol, 3-aminopropanol, 1-amino-2-propanol, 1-amino-2-methyl-2-propanol, 2-amino-2-methyl-1-propanol, 4-amino-1-butanol, 6-amino-1-hexanol, 10-amino-1-decanol, 12-amino-1-dodecanol, N-methyl-2-aminoethanol, N-ethyl-2-aminoethanol, N-propyl-2-aminoethanol, 2-dimethylaminoethanol, 6-diethylaminohexanol, 1-(2-hydroxyethyl)pyrrolidine, 2-(hydroxymethyl)pyrrolidine, 2-(2-hydroxyethyl)-1-methylpyrrolidine, 1-piperidineethanol, 1-ethanol-4-propanolpiperidine, etc.
[0137] Examples of the aforementioned dialkyl alcoholamines include: diethanolamine, di-n-propanolamine, diisopropanolamine, di-n-butanolamine, diisobutanolamine, N-methyldiethanolamine, etc.
[0138] Examples of the aforementioned trialkylolamines include triethanolamine, tri-n-propanolamine, triisopropanolamine, tri-n-butanolamine, and triisobutanolamine.
[0139] Examples of the aforementioned aminoalkane diols include: 1-amino-2,3-propanediol, 4-amino-1,2-butanediol, 4-amino-1,3-butanediol, 2-amino-1,3-propanediol, 2-amino-2-methyl-1,3-propanediol, 1-methylamino-2,3-propanediol, 1-ethylamino-2,3-propanediol, 1-propylamino-2,3-propanediol, 1-butylamino-2,3-propanediol, 3-dimethylamino-1,2-propanediol, and 2-diethylamino-1,3-propanediol.
[0140] Examples of the aforementioned diamines include: 1,3-propanediamine, 2,2-dimethyl-1,3-propanediamine, 1,4-butanediamine, 1,5-pentanediamine, 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,5-diamino-2-methylpentane, N,N'-dimethylethylenediamine, N,N'-diethylethylenediamine, N,N'-dimethyl-1,3-propanediamine, N,N'-diethyl-1,3-propanediamine, N,N'-dimethyl-1,4-butanediamine, N,N'-diethyl-1 4-Butanediamine, N,N'-dimethyl-1,6-hexanediamine, N,N-dimethylethylenediamine, N,N-diethylethylenediamine, N,N-dimethyl-1,3-propanediamine, N,N-diethyl-1,3-propanediamine, N,N-dimethyl-1,4-butanediamine, N,N-diethyl-1,4-butanediamine, N,N-dimethyl-1,6-hexanediamine, 1,2-cyclohexanediamine, 1,4-cyclohexanediamine, piperazine, N-methylpiperazine, N-ethylpiperazine, N,N'-dimethylpiperazine, homopiperazine, etc.
[0141] Examples of the aforementioned triamines include: diethylenetriamine, N,N,N',N”,N”-pentamethyldiethylenetriamine, N,N,N',N”,N”-penta(2-hydroxypropyl)diethylenetriamine, 3,3'-diaminodipropylamine, N-(3-aminopropyl)-N-methyl-1,3-propanediamine, N'-[3-(dimethylamino)propyl]-N,N-dimethyl-1,3-propanediamine, 2,6,10-trimethyl-2,6,10-triazaundecane, N-(2-aminoethyl)piperazine, 1,4,7-triazacyclononane, N,N,N',N”,N”-penta(2-hydroxypropyl)diethylenetriamine, 1-(2-aminoethyl)-4-methylpiperazine, 1-(2-dimethylaminoethyl)-4-methylpiperazine, etc.
[0142] Examples of the aforementioned diaminoalkanols include: 1,3-diaminopropane-2-ol, 2-(2-aminoethylamino)ethanol, 2-(2-aminopropylamino)ethanol, 2-(2-aminoethylmethylamino)ethanol, 1-(2-hydroxyethyl)piperazine, 4-methylpiperazine-1-ethanol, 1,4-bis(2-hydroxyethyl)piperazine, etc.
[0143] Examples of the aforementioned imidazole compounds include: imidazole, 2-methylimidazolium, 2-propylimidazolium, N-methylimidazolium, N-propylimidazolium, N-butylimidazolium, 1-(2-hydroxyethyl)imidazolium, 2-ethyl-4-methylimidazolium, 1,2-dimethylimidazolium, 1-benzyl-2-methylimidazolium, 1-cyanoethyl-2-methylimidazolium, 1-cyanoethyl-2-ethyl-4-methylimidazolium, 2-phenyl-4,5-dihydroxymethylimidazolium, 1-acetylimidazolium, 2-hydroxybenzimidazole, etc.
[0144] Examples of nitrogen-containing aromatic compounds mentioned above include: pyridine, α-methylpyridine, β-methylpyridine, γ-methylpyridine, 2,6-dimethylpyridine, 2,3-dimethylpyridine, pyrazine, 2-hydroxypyrazine, pyrimidine, 2-hydroxypyrimidine, 4-hydroxypyrimidine, pyridazine, 3-hydroxypyridazine, 4-hydroxypyridazine, triazine, 2-hydroxytriazine, etc.
[0145] From the viewpoint that metal ions can be easily stabilized through chelation coordination, the basic compound included in the above composition is preferably a basic compound with chelation coordination properties having an ethylenediamine structure or an ethanolamine structure in its molecular structure. The amino group in the above structure can be any amino group among primary amino, secondary amino, and tertiary amino groups, and from the viewpoint of suppressing side reactions between the basic compound and reducing organic compounds, a tertiary amino group is preferred.
[0146] The aforementioned basic compound preferably contains, in addition to the basic compound with the aforementioned chelating coordination properties, an alkylamine having at least one straight-chain alkyl group having 1 to 20 carbon atoms (preferably 1 to 15 carbon atoms).
[0147] In the above composition, the molar ratio (basic group / acidic group) of the basic group of the basic compound to the acidic group of the reducing organic compound is 0.4 or more, preferably 0.5 or more, more preferably 0.6 or more, further preferably 1.0 or more, and particularly preferably 1.6 or more. When the above molar ratio is less than 0.4, the reducing organic compound may sometimes react with the metal based on the acidic group, and the composition (especially the paste) may become a solid in a coagulated state and be unable to maintain the paste state. The above molar ratio is preferably 2.0 or less, more preferably 1.8 or less, and further preferably 1.7 or less. When the above molar ratio is 2.0 or less, the surface of the composite particles of this disclosure is easily reduced, which makes the sintered body have excellent conductivity. It should be noted that the number of moles of acidic groups contained in the reducing organic compound refers to the value obtained by multiplying the number of moles of the reducing organic compound by the number of acidic groups contained in the reducing organic compound, and the number of moles of basic groups contained in the basic compound refers to the value obtained by multiplying the number of moles of the basic compound by the number of basic groups contained in the basic compound.
[0148] The proportion of the alkaline compound in the composition relative to the total amount (100% by mass) is preferably 0.1 to 10% by mass, more preferably 0.3 to 9% by mass, and even more preferably 0.5 to 8% by mass.
[0149] <Coordination Organic Compounds>
[0150] The aforementioned coordination organic compound is a compound located on the metal surface of the composite particles of this disclosure, and is other than the compounds belonging to the aforementioned basic compounds. Preferably, the aforementioned coordination organic compound has a boiling point higher than at least one of the aforementioned reducing organic compounds. In this case, the aforementioned coordination organic compound is more likely to remain during calcination than the aforementioned reducing organic compounds, and it is easier to inhibit the contact between the aforementioned reducing organic compounds and the active metal surface; therefore, the decomposition of the aforementioned reducing organic compounds is suppressed.
[0151] Examples of such coordinating organic compounds include at least one compound selected from compounds having a carboxyl group, compounds having a ketone group (e.g., diketones such as acetylacetone, β-keto esters, etc.), compounds having a hydroxyl group, compounds having a sulfonyl group, and compounds having a thiol group.
[0152] The compounds containing carboxyl groups are preferably monocarboxylic acids or dicarboxylic acids, more preferably monocarboxylic acids.
[0153] The aforementioned carboxylic acids can be those identical to those described for the reducing organic compounds. Furthermore, from the viewpoint of being readily available and having low toxicity and odor, they can be carboxylic acids with 2 to 15 carbon atoms (preferably 5 to 12, more preferably 8 to 10). Specific examples include: acetic acid (boiling point 118°C), lactic acid (boiling point 122°C), propionic acid (boiling point 141°C), acrylic acid (boiling point 141°C), malic acid (boiling point 167°C), valeric acid (boiling point 186°C), hexanoic acid (boiling point 205°C), heptanoic acid (boiling point 223°C), 2-ethylhexanoic acid (boiling point 228°C), succinic acid (boiling point 235°C), octanoic acid (boiling point 237°C), nonanoic acid (boiling point 254°C), decanoic acid (boiling point 269°C), dodecanoic acid (boiling point 299°C), tartaric acid (boiling point 275°C), and oxalic acid (boiling point 365°C). Since carboxylic acids function as both reducing and coordinating organic compounds, when using a carboxylic acid as a coordinating organic compound, it is sufficient to combine it with other carboxylic acids having higher boiling points than the one with the lowest boiling point. In this case, the carboxylic acid with the relatively higher boiling point primarily functions as a protecting agent, while the carboxylic acid with the relatively lower boiling point primarily functions as a reducing agent.
[0154] From the viewpoint that it is less volatile than formic acid (boiling point 101°C), the above-mentioned carboxylic acid preferably has a boiling point of more than 110°C under normal pressure, more preferably more than 150°C, and even more preferably more than 200°C.
[0155] In the above composition, the ratio of the molar number of coordinating functional groups in the coordinating organic compound to the molar number of acidic groups in the reducing organic compound (coordinating functional group / acidic group) is preferably 0.05 to 1.20, more preferably 0.40 to 1.10, and even more preferably 0.50 to 0.70. When the above molar ratio is 0.05 or higher, it is easy to obtain the precipitation of small-diameter metal particles; when the above molar ratio is 1.20 or lower, the coordinating organic compound is less likely to remain during firing.
[0156] The molar ratio (coordinating functional group / basic compound) of the coordination organic compound in the above composition to the basic group of the basic compound is preferably 0.10 to 1.00, more preferably 0.15 to 0.75, and even more preferably 0.20 to 0.60. When the above molar ratio is 0.10 or higher, it is easy to obtain the precipitation of small-diameter metal particles, and when the above molar ratio is 1.00 or lower, the coordination organic compound is less likely to remain during firing.
[0157] The proportion of the coordinating organic compound in the composition relative to the total amount (100% by mass) is preferably 0.1 to 10% by mass, more preferably 0.2 to 9% by mass, and even more preferably 0.3 to 8% by mass.
[0158] <Resin>
[0159] Examples of the aforementioned resins include: thermoplastic resins (polyester resins, polyamide resins, polyurethane resins, polyimide resins, polyolefin resins, (meth)acrylic resins, styrene resins, halogenated vinyl resins, polyvinyl acetal resins, cellulose resins (ethyl cellulose resins, alkyl cellulose resins, etc.), thermoplastic silicone resins, etc.) and thermosetting resins (epoxy resins, unsaturated polyester resins, diallyl phthalate resins, silicone resins, etc.). Among these, thermoplastic resins are preferred from the viewpoint of mitigating internal stress during heating.
[0160] Relative to the total amount (100% by mass) of the above composition, the content of the above resin in the above composition is preferably 1.0% by mass or less, more preferably 0.05 to 1.0% by mass, and even more preferably 0.1 to 0.9% by mass.
[0161] <Organic solvents>
[0162] To adjust flowability (viscosity) and workability, the above composition may also contain an organic solvent. The organic solvent is preferably an organic solvent comprising at least organic solvent (a), organic solvent (b), and organic solvent (c). Organic solvent (a), organic solvent (b), and organic solvent (c) are different compounds and satisfy the following formulas (1) to (6). Only one of organic solvent (a), organic solvent (b), and organic solvent (c) may be used, or two or more may be used.
[0163] 150℃≤Ta≤250℃ (1)
[0164] 150℃≤Tb≤250℃ (2)
[0165] 250℃≤Tc≤350℃ (3)
[0166] δa≥10.0 (4)
[0167] δc≤9.0 (5)
[0168] δc≤δb≤δa (6)
[0169] In the formula, Ta~Tc represent the boiling points of organic solvents (a)~(c), respectively, and δa~δc represent the Hansen solubility parameters of organic solvents (a)~(c), respectively. It should be noted that in this specification, the Hansen solubility parameter is referred to as the "SP value", and sometimes expressed as "δ".
[0170] It should be noted that the organic solvents (a) to (c) are any solvents that can be uniformly dissolved into a liquid state when mixed in the proportions used in the above compositions. Each of them can be liquid or solid at room temperature.
[0171] The organic solvent (a) at least satisfies formula (1). That is, the boiling point Ta of the organic solvent (a) satisfies 150℃≤Ta≤250℃, preferably 150℃<Ta<250℃, more preferably 155℃≤Ta≤220℃, and even more preferably 160℃≤Ta≤200℃. By using an organic solvent (a) with a boiling point within the above range, the organic solvent readily volatilizes during sintering, making it easy to form a sintered body.
[0172] The organic solvent (a) at least satisfies formula (4) [δa ≥ 10.0]. The SP value δa of the organic solvent (a) is 10.0 or more, preferably 10.3 or more, and more preferably 10.4 or more, within the range satisfying formula (6). By making the above-mentioned δa 10.0 or more, the composite particles of the present disclosure have excellent dispersibility, and the separation of metal particles from organic solvent is less likely to occur. The δa of the organic solvent (a) is, for example, 16.0 or less, and can be 15.0 or less.
[0173] Examples of the organic solvent (a) include alcohol solvents, urea-based solvents, aprotic polar solvents, and the like. Examples of the alcohol solvent include compounds having one or more hydroxyl groups, among which tertiary alcohols and ether alcohols are preferred. The alcohol solvent may also have two or more hydroxyl groups. The ether alcohol is a compound having an ether bond and a hydroxyl group, and examples thereof include (poly)alkylene glycol monoalkyl ethers, alkoxy-substituted alcohols, and the like.
[0174] Specific examples of the organic solvent (a) include pinacol (δ 10.7, boiling point 172°C), tetramethylurea (δ 10.6, boiling point 177°C), 3-methoxybutanol (δ 10.6, boiling point 161°C), 1-methylcyclohexanol (δ 10.4, boiling point 155°C), methyl carbitol (diethylene glycol monomethyl ether) (δ 10.7, boiling point 193°C), and the like.
[0175] The organic solvent (b) at least satisfies formula (2). That is, the boiling point Tb of the organic solvent (b) satisfies 150°C ≤ Tb ≤ 250°C, preferably 150°C < Tb < 250°C, more preferably 180°C ≤ Tb ≤ 248°C, and even more preferably 200°C ≤ Tb ≤ 245°C. By using the organic solvent (b) having a boiling point within the above range, the organic solvent is easily volatilized during sintering, and a sintered body can be easily formed. In addition, by using the organic solvent (b) having a boiling point of 250°C or lower, the generation of voids during sintering can be suppressed.
[0176] The organic solvent (b) at least satisfies formula (6). The SP value δb of the organic solvent (b) in the range satisfying formula (6) is preferably 8.0 to 12.0, more preferably 8.5 to 11.0, and even more preferably 9.0 to 10.5. When the above δb is within the above range, the compatibility of the organic solvent (a) and the organic solvent (c) is improved, separation is less likely to occur, and there is a tendency that the continuous discharge stability and storage stability are more excellent.
[0177] Examples of the organic solvent (b) include alcohol solvents, ester solvents, ketone solvents, amine-based solvents, and the like. Examples of the alcohol solvent include solvent compounds having one or more hydroxyl groups, among which tertiary alcohols, ether alcohols, and ester alcohols are preferred. The ether alcohol is a compound having an ether bond and a hydroxyl group, and examples thereof include (poly)alkylene glycol monoalkyl ethers, alkoxy-substituted alcohols, and the like. The ester alcohol is a compound having an ester bond and a hydroxyl group, and examples thereof include (poly)alkylene glycol monoalkyl ether monoesters and the like. Examples of the ester solvent include diacetates of diols such as (poly)alkylene glycols and the like. As the ketone solvent, cyclic ketones are preferred. As the amine-based solvent, alkylamines are preferred.
[0178] As an organic solvent (b), it can be selected based on the premise that it satisfies equation (6) in relation to organic solvents (a) and (c). Specifically, it can be used for example: d-Camphor (δ10.4, boiling point 204℃), 1-Heptanol (δ10.0, boiling point 177℃), butylcarbitol (diethylene glycol monobutyl ether) (δ10.2, boiling point 231℃), ethylcarbitol (diethylene glycol monoethyl ether) (δ10.5, boiling point 196℃), tripropylene glycol monomethyl ether (δ9.4, boiling point 243℃), α-terpineol (δ9.3... The following are listed: dihydroterpineol (δ 9.0, boiling point 210℃), 1,3-butanediol diacetate (δ 9.2, boiling point 232℃), propylene glycol diacetate (δ 9.3, boiling point 190℃), butyl carbitol acetate (δ 9.0, boiling point 247℃), dipropylene glycol butyl ether (δ 9.2, boiling point 230℃), isophorone (δ 9.5, boiling point 213℃), 1-decyl alcohol (δ 9.6, boiling point 230℃), propylene glycol monobutyl ether (δ 9.0, boiling point 170℃), 1-nonanol (δ 9.8, boiling point 214℃), etc.
[0179] The boiling point Tb of the organic solvent (b) is preferably higher than the boiling point Ta of the organic solvent (a), that is, preferably Tb > Ta. The temperature difference between Tb and Ta [Tb-Ta] is preferably 2°C or more, more preferably 5°C or more, and even more preferably 10°C or more. When the above temperature difference is 2°C or more, the generation of voids during sintering can be further suppressed.
[0180] The organic solvent (c) at least satisfies equation (3). That is, the boiling point Tc of the organic solvent (c) satisfies 250℃≤Tc≤350℃, preferably 250℃<Tc<350℃, more preferably 250℃<Tc≤320℃, and even more preferably 250℃<Tc≤300℃. By using an organic solvent (c) with a boiling point within the above range, the rapid volatilization of organic solvent (a) and organic solvent (b) during sintering can be suppressed, thereby suppressing the formation of voids.
[0181] The organic solvent (c) must at least satisfy formula (5) [δc ≤ 9.0]. The SP value δc of the organic solvent (c) is 9.0 or less, preferably 8.7 or less, and more preferably 8.5 or less. By making the above-mentioned δc 9.0 or less, the generation of voids during sintering can be suppressed. The δc of the organic solvent (c) is, for example, 6.0 or more, and can be 7.0 or more.
[0182] Examples of organic solvents (c) include ether solvents, alkane solvents, and ester solvents. Examples of ether solvents include (poly)alkylene glycol dialkyl ethers. Examples of alkane solvents are alkanes with 14 or more carbon atoms (e.g., 14 to 20 carbon atoms). Examples of ester solvents are esters of (poly)alkylene glycol alkyl ethers and fatty acids.
[0183] Examples of organic solvents (c) include: dibutylcarbitol (diethylene glycol dibutyl ether) (δ8.3, boiling point 255℃), tetradecane (δ7.9, boiling point 254℃), hexadecane (δ8.0, boiling point 287℃), etc.
[0184] The boiling point Tc of the organic solvent (c) is preferably higher than the boiling point Tb of the organic solvent (b), that is, preferably Tc > Tb. The temperature difference between Tc and Tb [Tc-Tb] is preferably 2°C or more, more preferably 6°C or more, and even more preferably 10°C or more. When the above temperature difference is 2°C or more, the generation of voids during sintering can be further suppressed.
[0185] The boiling point Tc of the organic solvent (c) is preferably higher than the boiling point Ta of the organic solvent (a), that is, preferably Tc > Ta. The temperature difference between Tc and Ta [Tc-Ta] is preferably 30°C or more, more preferably 50°C or more, and even more preferably 60°C or more. When the above temperature difference is 30°C or more, the generation of voids during sintering can be further suppressed.
[0186] The SP values δa, δb, and δc of organic solvent (a), organic solvent (b), and organic solvent (c) satisfy the relationship [δc ≤ δb ≤ δa] of the above equation (6). Preferably, δb is higher than δc, i.e., preferably δc < δb. Furthermore, preferably, δa is higher than δb, i.e., preferably δb < δa.
[0187] The difference between δb and δc [δb-δc] is preferably 0.1 or more, more preferably 0.2 or more, and even more preferably 0.5 or more. When the difference is 0.1 or more, the dispersibility of the metal particles is better, and the continuous discharge stability is better. The difference is preferably 2.0 or less, more preferably 1.5 or less, and even more preferably 1.3 or less. When the difference is 2.0 or less, the composite particles of this disclosure are not easily separated from the organic solvent, and the continuous discharge stability and storage stability are better.
[0188] The difference between δa and δb [δa-δb] is preferably 0.1 or more, more preferably 0.2 or more, and even more preferably 0.5 or more. When the difference is 0.1 or more, the dispersibility of the metal particles is better, and the continuous discharge stability is better. The difference is preferably 2.5 or less, more preferably 2.0 or less, and even more preferably 1.8 or less. When the difference is 2.5 or less, the metal particles are less likely to separate from the organic solvent, and the continuous discharge stability and storage stability are better.
[0189] Based on equations (4) and (5), the difference between δa and δc [δa-δc] is 1.0 or more, preferably 1.5 or more, and more preferably 2.0 or more. When the difference is 1.0 or more, the generation of voids during sintering can be further suppressed. The difference is preferably 5.0 or less, more preferably 4.0 or less, and even more preferably 3.0 or less. When the difference is 5.0 or less, the composite particles of this disclosure are not easily separated from the organic solvent, and the continuous discharge stability and storage stability are better.
[0190] The ratio of organic solvent (a) to the total amount of organic solvent (a), organic solvent (b), and organic solvent (c) in 100% by mass [organic solvent (a) / {organic solvent (a) + organic solvent (b) + organic solvent (c)}] is preferably 5 to 70% by mass, more preferably 10 to 60% by mass, and even more preferably 15 to 50% by mass. When the above ratio is within the above range, the organic solvent is easy to volatilize during sintering, which can easily form a sintered body, and the dispersibility with the composite particles of this disclosure is better.
[0191] The ratio of organic solvent (b) to the total amount of organic solvent (a), organic solvent (b) and organic solvent (c) in a 100% mass percentage [organic solvent (b) / {organic solvent (a) + organic solvent (b) + organic solvent (c)}] is preferably 5 to 70% by mass, more preferably 10 to 60% by mass, and even more preferably 15 to 50% by mass. When the above ratios are within the above ranges, the compatibility of each organic solvent is excellent, and the continuous discharge stability and storage stability are even better.
[0192] The ratio of organic solvent (c) to the total amount of organic solvent (a), organic solvent (b), and organic solvent (c) in 100% by mass [organic solvent (c) / {organic solvent (a) + organic solvent (b) + organic solvent (c)}] is preferably 5 to 70% by mass, more preferably 10 to 60% by mass, and even more preferably 15 to 50% by mass. When the above ratio is within the above range, the generation of voids during sintering can be further suppressed.
[0193] The content of organic solvent (c) relative to 100 parts by mass of organic solvent (a) is preferably 20 to 400 parts by mass, more preferably 30 to 300 parts by mass, and even more preferably 50 to 200 parts by mass. When the above content is within the above range, the balance of the proportions of organic solvent (a) and organic solvent (c) is good, and the void suppression during sintering and the dispersibility with the composite particles of this disclosure are better.
[0194] Relative to the combined mass of organic solvent (a) and organic solvent (c) of 100 parts by mass, the content of organic solvent (b) is preferably 10 to 200 parts by mass, more preferably 20 to 150 parts by mass, and even more preferably 40 to 100 parts by mass. When the content is within the above range, the compatibility between organic solvent (a) and organic solvent (c) is further improved, and the continuous discharge stability and low-temperature storage performance are superior.
[0195] The aforementioned organic solvents may also include other solvents (organic solvents) besides organic solvent (a), organic solvent (b), and organic solvent (c). The total content of organic solvents (a), (b), and (c) relative to 100% by mass is preferably 50% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, more preferably 90% by mass or more, and particularly preferably 95% by mass or more. When the content is 50% by mass or more, the dispersibility with the composite particles of this disclosure and the compatibility with each organic solvent are superior, as are the continuous discharge stability, storage stability, and void formation suppression during sintering.
[0196] When organic solvent (a), organic solvent (b), and organic solvent (c) are mixed in the proportions used in the above composition, organic solvent (a), organic solvent (b), and organic solvent (c) preferably dissolve uniformly at room temperature without phase separation. Furthermore, in the above composition, organic solvent (a), organic solvent (b), and organic solvent (c) preferably dissolve uniformly at room temperature without phase separation. Particularly, it is preferable that phase separation does not occur at 22-28°C (preferably 10-30°C, more preferably 0-35°C).
[0197] In the above composition, the content of the organic solvent is preferably 0.5 to 30 parts by mass, more preferably 2 to 20 parts by mass, relative to 100 parts by mass of the composite particles of this disclosure and the organic matter other than the organic solvent.
[0198] [Method for manufacturing the composition]
[0199] As one embodiment of this disclosure, a method for manufacturing a composition is provided. The composition comprises composite particles on which a metal is supported on a substrate particle and a solvent. The manufacturing method includes a step of irradiating a composition (A) containing the substrate particle, a metal compound that is a raw material for the metal, and a solvent with ultrasound in order to manufacture the composite particles. The manufacturing method yields a composition with a particle sintering rate of 30% or more as expressed by the following formula (1).
[0200] Particle sintering rate = (Total number of substrate particles with a length of 100 nm or more oriented in at least one direction and bonded to the bonded material in an image obtained by taking a cross-section of the sintered body after the following sintering process at 20,000x magnification using FE-SEM) / (Total number of substrate particles with a length of 100 nm or more oriented in at least one direction in an image obtained by taking a cross-section of the sintered body after the following sintering process at 20,000x magnification using FE-SEM) (1)
[0201] Sintering process: The above composition is printed on a Cu substrate with a 2μm thick Ag coating using a metal mask (5mm opening, 0.15mm mask thickness). The Cu substrate is placed on a heating plate maintained at 100°C and held for 1 minute. Then it is removed from the heating plate and allowed to return to room temperature. The Cu substrate is then placed on a heating plate maintained at 250°C and held for 30 minutes. Then it is removed from the heating plate and allowed to return to room temperature.
[0202] There are no particular limitations on the method for manufacturing the above composition. For example, it can be manufactured by pre-mixing the above composite particles with components other than the solvent, and then adding the solvent and mixing them using a known or conventional method. Alternatively, the above composite particles can be manufactured using the method described above.
[0203] (Sintered body)
[0204] A sintered body can be produced by sintering the above composition. The heat treatment temperature during sintering is preferably 150-400°C, more preferably 180-350°C, and even more preferably 200-300°C. By keeping the heat treatment temperature below 400°C, the influence of the heat treatment on the substrate and the bonded material can be suppressed. Furthermore, the sintering time is preferably, for example, 10 seconds to 2 hours, more preferably 3 minutes to 1 hour. Moreover, the above sintered body can be a sintered body sintered without pressure or a sintered body sintered under pressure. In the case of pressure, the pressure applied is, for example, 0.3-40 MPa.
[0205] The sintered body produced as described above can be used, for example, as a bonding body for joining a substrate to an object.
[0206] (Joint)
[0207] As a method for manufacturing the aforementioned bond, it can be manufactured by coating the composite particles or the aforementioned composition disclosed herein onto a substrate using a printing method (specifically, dispensing printing, mask printing, screen printing, inkjet printing, etc.), mounting the bonded object on the coating layer, and then sintering. Furthermore, the sintering conditions can be the same as those used in the case of manufacturing the sintered body described above.
[0208] The thickness of the above-mentioned joint is preferably 5~500μm, more preferably 20~300μm, and even more preferably 40~150μm.
[0209] Examples of substrates mentioned above include: metal substrates such as copper substrates, ceramic substrates, metal-ceramic substrates, SiC substrates, gallium nitride substrates, glass epoxy boards, BT resin substrates, glass substrates, and resin substrates.
[0210] Examples of materials to be joined include electronic components and heat sinks. Examples of electronic components include semiconductor elements, LED elements, and other electronic components (chips, dies). Specifically, examples of semiconductor elements include power semiconductor elements. Examples of materials to be joined include Si (silicon), SiC (silicon carbide), GaN, and diamond.
[0211] The aforementioned bond, manufactured in this way, bonds the substrate and the workpiece together using composite particles of the present disclosure that can be sintered at low temperatures and have excellent heat resistance, thus resulting in a bond with excellent heat resistance. Furthermore, since it can be manufactured through heat treatment at relatively low temperatures, bonding can be achieved even with ordinary materials.
[0212] The various methods disclosed in this specification can also be combined with any other features disclosed in this specification. Furthermore, the various configurations and combinations thereof in each embodiment are examples, and appropriate additions, omissions, and other modifications can be made without departing from the spirit of the invention. The invention is not limited to the embodiments, but only to the scope of the claims.
[0213] Example
[0214] Hereinafter, an embodiment of the present invention will be described in more detail based on an example.
[0215] Manufacturing Example 1
[0216] Using 2.2 parts by mass of Ag₂O powder, 1 part by mass of silicon particles (Si purity > 99.999%, particle size D50 = 0.56 μm) as the substrate particles, and 100 ml of ethanol as the solvent, the above raw materials were mixed in a 300 ml Erlenmeyer flask and subjected to ultrasonic irradiation for 24 hours at a temperature of 40°C, a frequency of 50 kHz, and an output of 100 W to produce Ag-loaded silicon particles of Manufacturing Example 1. It should be noted that in the Ag-loaded silicon particles of Manufacturing Example 1, 10% by volume of Ag was loaded relative to 90% by volume of silicon particles. The average particle size D50 of the loaded Ag was 50 nm.
[0217] Manufacturing Example 2
[0218] As the substrate particles, 1 part by mass of SiO2 particles (manufactured by Sakai Chemical Industry, particle size D50 = 0.4 μm) was used. Otherwise, Ag-loaded SiO2 particles of Manufacturing Example 2 were prepared using the same method as in Manufacturing Example 1. It should be noted that in the Ag-loaded SiO2 particles of Manufacturing Example 2, 10 vol% Ag was loaded relative to 90 vol% of the SiO2 particles. The average particle size D50 of the loaded Ag was 100 nm.
[0219] Manufacturing Example 3
[0220] Using a 3D ball mill (trade name "3D Ball Mill", manufactured by NAGAO SYSTEM), 75 parts by mass of silver flakes (trade name "AgC-239", manufactured by Fukuda Metal Foil Powder Industry Co., Ltd.) and 25 parts by mass of silicon particles (Si purity > 98.9%, particle size D50 = 32.8 μm) were mixed and pulverized to obtain Ag-silicon mixed particles of Manufacturing Example 3. It should be noted that in the Ag-silicon mixed particles of Manufacturing Example 3, 40% by volume of Ag is supported relative to 60% by volume of silicon particles.
[0221] Example 1
[0222] 70 parts by volume of silver flakes (trade name "AgC-239", manufactured by Fukuda Metal Foil Powder Industry Co., Ltd.) were mixed with 30 parts by volume of Ag-loaded silicon particles from Manufacturing Example 1, and the resulting mixed particles were referred to as loaded mixed particles A. The volume ratio of silicon to Ag in loaded mixed particles A was 30:70. As a solvent, "CELTOL IA" (manufactured by Daicel Co., Ltd.) was used, and the mixture was added by weight to achieve the above-mentioned loaded mixed particles A: CELTOL IA = 8.2: 1.0, and then manually mixed to prepare a paste-like composition of Example 1.
[0223] Example 2
[0224] 70 parts by volume of silver flakes (trade name "AgC-239", manufactured by Fukuda Metal Foil Powder Industry Co., Ltd.) were mixed with 30 parts by volume of Ag-loaded SiO2 particles from Manufacturing Example 2, and the resulting mixed particles were referred to as loaded mixed particles B. The volume ratio of SiO2 particles to Ag in loaded mixed particles B was 30:70. As a solvent, "CELTOL IA" (manufactured by Daicel Co., Ltd.) was used, and the mixture was added by weight to achieve a loading ratio of loaded mixed particles B: CELTOL IA = 10.0: 1.0, and manually mixed to prepare a paste-like composition of Example 2.
[0225] Comparative Example 1
[0226] 70 parts by volume of silver flakes (trade name "AgC-239", manufactured by Fukuda Metal Foil Powder Industry Co., Ltd.) and 30 parts by volume of silicon particles (Si purity > 99.999%, particle size D50 = 0.56 μm) were mixed, and the resulting mixed particles were referred to as mixed particles A. As a solvent, "CELTOL IA" (manufactured by Daicel Co., Ltd.) was added at a weight ratio of mixed particles A: CELTOL IA = 8.2: 1.0, and the mixture was manually mixed to prepare a paste-like composition of Comparative Example 1.
[0227] Comparative Example 2
[0228] 70 parts by volume of silver flakes (trade name "AgC-239", manufactured by Fukuda Metal Foil Powder Industry Co., Ltd.) were mixed with 30 parts by volume of Ag and silicon mixed particles from Manufacturing Example 3, and the resulting mixed particles were referred to as mixed particles B. The volume ratio of silicon to Ag in mixed particles B was 30:70. As a solvent, "CELTOL IA" (manufactured by Daicel Co., Ltd.) was used, and the mixture was added by weight to achieve the above-mentioned mixed particles B:CELTOL IA = 8.2:1.0, and then manually mixed to prepare a paste-like composition of Comparative Example 2.
[0229] It should be noted that, in this disclosure, regarding the solvent-to-powder ratio when preparing the composition, since the viscosity of the printable paste varies depending on the particle size and shape of the powder, the amount of solvent will differ for different types of particles, but the difference in the amount of solvent will not affect the evaluation of sinterability.
[0230] [evaluate]
[0231] The compositions of the above-prepared examples and comparative examples were evaluated as follows, and the results are recorded in Table 1. It should be noted that, unless otherwise specified, the contents of Table 1 are recorded in parts by volume.
[0232] (1) Particle sintering rate
[0233] Using the compositions prepared in the examples and comparative examples, the compositions were printed onto a Cu substrate with a 2 μm thick Ag coating using a metal mask (5 mm opening, 0.15 mm mask thickness), and sintered by heating with a hot plate. Specifically, the Cu substrate was placed on a hot plate set to 100°C and held for 1 minute, then removed from the hot plate and allowed to return to room temperature. Then, the Cu substrate was placed on a hot plate held at 250°C and held for 30 minutes, then removed from the hot plate and allowed to return to room temperature, thereby producing sintered bodies of the compositions of the examples and comparative examples.
[0234] Using FE-SEM, the cross-section of the sintered body of the paste of the above-mentioned examples and comparative examples was observed at a magnification of 20,000. The number of particles (silicon particles, silicon particles loaded with Ag, SiO2 particles loaded with Ag) with a length of 100 nm or more in at least any direction that could be confirmed by visual observation, and the number of the above particles bonded to the bonded material such as silver flakes and Ag plating on Cu substrates, were measured. The proportion of sintered particles in the particles of 100 nm or more was calculated as the particle sintering rate using the following formula (1), and the results are shown in Table 1.
[0235] Particle sintering rate = (Total number of particles with a length of 100 nm or more oriented in at least one direction and bonded to the bonded material in an image obtained by FE-SEM at 20,000x magnification after sintering) / (Total number of particles with a length of 100 nm or more oriented in at least one direction in an image obtained by FE-SEM at 20,000x magnification after sintering) (1)
[0236] (2) Unit sintering rate
[0237] The unit sintering rate was calculated according to the method shown in equation (2) below, and the results are shown in Table 1.
[0238] Unit sintering rate = (particle sintering rate) / (volume ratio of Ag and / or Cu supported relative to substrate particles) (2)
[0239] Figure 2 The image is an FE-SEM image obtained by photographing a cross-section of the sintered body of Example 1. It can be confirmed that the sintered composite particles 1 are bonded to the silver flakes 23, which are particles other than the composite particles. In particular, since the Ag particles supported on the surface of the composite particles 1 have the effect of significantly reducing the contact angle with the silver flakes 23, the interface formation ability is improved, and the silver flakes spread out. Therefore, it can be confirmed that the composite particles 1 and the silver flakes 23 are bonded together over a large area.
[0240] Figure 3 The image is an FE-SEM image obtained by photographing a cross-section of the sintered body of Example 2. It can be confirmed that the sintered composite particles 1 are bonded to the silver flakes 24, which are particles other than composite particles, over a large area. In addition, although not shown, it can be confirmed that the sintered composite particles 1 are bonded to the Cu substrate after the Ag coating is applied. The composite particles 1 are not simply particles coated with Ag, but particles with self-sintering properties like Ag nanoparticles and Ag flake particles.
[0241] As according to Figure 2 ,3 As can also be confirmed, for the composition of the embodiment, the sintering rate of the particles in the sintered body reaches more than 30%, confirming that it is fully bonded to the bonded object and achieves a strong bond. The composition of this embodiment contains Ag and / or Cu supported on the above-mentioned substrate particles, which are particles selected from one or more raw materials selected from Si, W, SiO2, Cr and Mo. It is envisioned that it can be sintered at low temperature and exhibit heat resistance.
[0242] On the other hand, the FE-SEM image obtained by photographing the cross-section of the sintered body of Comparative Example 1 is shown below. Figure 4 Although there are areas where silicon particles 3 and silver flakes 25 are bonded together, bonding between silicon particles 3 and silver flakes 25 cannot be confirmed over a large area. The interface formation ability of silver flakes 25 on the surface of silicon particles 3 is insufficient, and the particle sintering rate is less than 30%, so bonding cannot be sufficiently achieved. Similarly, for the composition of Comparative Example 2, the particle sintering rate is also less than 30%, so bonding cannot be sufficiently achieved.
[0243] The following describes variations of the present invention.
[0244] [Postscript 1]
[0245] A composition comprising composite particles, an organic compound, and particles containing Ag and / or Cu other than the aforementioned composite particles. The aforementioned composite particles comprise substrate particles and Ag and / or Cu supported on the substrate particles. The linear expansion coefficient of the aforementioned substrate particles is below 8 ppm / K. The particle sintering rate represented by the following formula (1) is 30% or more.
[0246] Particle sintering rate = (Total number of substrate particles with a length of 100 nm or more oriented in at least one direction and bonded to the bonded material in an image obtained by taking a cross-section of the sintered body after the following sintering process at 20,000x magnification using FE-SEM) / (Total number of substrate particles with a length of 100 nm or more oriented in at least one direction in an image obtained by taking a cross-section of the sintered body after the following sintering process at 20,000x magnification using FE-SEM) (1)
[0247] Sintering process: The above composition is printed on a Cu substrate with a 2μm thick Ag coating using a metal mask (5mm opening, 0.15mm mask thickness). The Cu substrate is placed on a heating plate maintained at 100°C and held for 1 minute. Then it is removed from the heating plate and allowed to return to room temperature. The Cu substrate is then placed on a heating plate maintained at 250°C and held for 30 minutes. Then it is removed from the heating plate and allowed to return to room temperature.
[0248] [Postscript 2]
[0249] According to the composition described in Appendix 1, the unit sintering rate represented by the following formula (2) is 0.7 or more.
[0250] Unit sintering rate = (particle sintering rate) / (the ratio of the volume of Ag and / or Cu supported to the volume of the substrate particles) (2)
[0251] It should be noted that when the volume of the substrate particles in the composite particles is set as VA and the volume ratio of the supported Ag and / or Cu is set as VB, the ratio of the volume of the supported Ag and / or Cu to the volume of the substrate particles is expressed by the following formula (3). (The ratio of the volume of Ag and / or Cu carried to the volume of the substrate particles) = VB / (VA + VB) (3).
[0252] [Postscript 3]
[0253] The composition according to Appendix 1 or 2, wherein the substrate particles are particles selected from Si, W, SiO2, Cr and Mo.
[0254] [Postscript 4]
[0255] The composition according to any one of Appendices 1 to 3, wherein the volume ratio of Ag and / or Cu in all the particles contained in the composition is 50 to 95% by volume.
[0256] [Postscript 5]
[0257] According to any one of Appendices 1 to 4, in the composition obtained by taking pictures of any 5 parts of the cross section of the above-mentioned composite particles using SEM at 1000x magnification, the average number of the following particle aggregates A is 2 or less.
[0258] Particle aggregate A: contains multiple substrate particles, and Ag and / or Cu, wherein the area ratio of the supported Ag and / or Cu is more than 70% relative to the substrate particles, and the diameter of the longest part of the aggregate is more than 5 μm.
[0259] [Postscript 6]
[0260] According to the composition described in Appendix 5, the number of the substrate particles contained in the particle agglomerate A is less than 30% of the total number of substrate particles.
[0261] [Postscript 7]
[0262] According to any one of Appendices 1 to 6, in the composition obtained by taking an image of the above-mentioned composite particles at 1000x magnification using SEM, the number of the following particle aggregates B is 2 or less.
[0263] Particle aggregate B: Contains multiple substrate particles, and Ag and / or Cu, wherein the area ratio of the supported Ag and / or Cu is more than 70% relative to the substrate particles, the porosity in the particle aggregate is less than 30% and the diameter of the longest part of the aggregate is more than 5 μm.
[0264] [Postscript 8]
[0265] According to the composition described in Appendix 7, the number of the substrate particles contained in the particle aggregate B is less than 30% of the total number of substrate particles.
[0266] [Postscript 9]
[0267] The composition according to any one of Appendices 1 to 8, wherein the Ag and / or Cu are uniformly granular and supported on the substrate particles in the form of Ag particles and / or Cu particles.
[0268] [Postscript 10]
[0269] The composition according to any one of Appendices 1 to 8, wherein the Ag and / or Cu are supported in a film-like manner on the substrate particles.
[0270] [Postscript 11]
[0271] According to the composition described in Appendix 9, the content of Ag in the above-mentioned Ag particles 100% by mass is 95% by mass or more.
[0272] [Postscript 12]
[0273] According to the composition described in Appendix 9, the content of Cu in 100% by mass of the Cu particles is 95% by mass or more.
[0274] [Postscript 13]
[0275] The composition according to any one of Appendices 9, 11 to 12, wherein the average particle size (median particle size) of the Ag particles and the Cu particles is 1 nm or more and 10,000 nm or less.
[0276] [Postscript 14]
[0277] The composition according to any one of Appendices 9, 11 to 12, wherein the average particle size (median particle size) of the Ag particles and the Cu particles is 5 nm or more and 1000 nm or less.
[0278] [Postscript 15]
[0279] The composition according to any one of Appendices 9, 11 to 12, wherein the average particle size (median particle size) of the Ag particles and the Cu particles is 10 nm or more and 500 nm or less.
[0280] [Postscript 16]
[0281] According to the composition described in Appendix 10, the Ag and / or Cu described above are supported on the substrate particles in a film-like manner, with a thickness of 10 nm to 10 μm.
[0282] [Postscript 17]
[0283] The composition according to any one of Appendices 1 to 16, wherein the average particle size of the substrate particles is 0.05 to 50 μm.
[0284] [Postscript 18]
[0285] A method for manufacturing a composition comprising a solvent and composite particles on which a metal is supported, wherein the composition comprises a solvent and composite particles on which a metal is supported, and a method for manufacturing a composition comprising ... The manufacturing method described above includes a step of irradiating a composition (A) containing the substrate particles, a metal compound that is a raw material for the metal, and a solvent with ultrasound in order to manufacture the composite particles described above. The above manufacturing method yields a composition with a particle sintering rate of 30% or more, expressed as in formula (1).
[0286] Particle sintering rate = (Total number of substrate particles with a length of 100 nm or more oriented in at least one direction and bonded to the bonded material in an image obtained by taking a cross-section of the sintered body after the following sintering process at 20,000x magnification using FE-SEM) / (Total number of substrate particles with a length of 100 nm or more oriented in at least one direction in an image obtained by taking a cross-section of the sintered body after the following sintering process at 20,000x magnification using FE-SEM) (1)
[0287] Sintering process: The above composition is printed on a Cu substrate with a 2μm thick Ag coating using a metal mask (5mm opening, 0.15mm mask thickness). The Cu substrate is placed on a heating plate maintained at 100°C and held for 1 minute. Then it is removed from the heating plate and allowed to return to room temperature. The Cu substrate is then placed on a heating plate maintained at 250°C and held for 30 minutes. Then it is removed from the heating plate and allowed to return to room temperature.
[0288] [Postscript 19]
[0289] According to the method for manufacturing the composition described in Appendix 18, in the process of irradiating ultrasound, the temperature of the composition (A) is 20 to 100°C.
[0290] [Postscript 20]
[0291] According to the method of manufacturing the composition described in Appendix 18 or 19, in the above-mentioned step of irradiating ultrasound, the irradiation conditions of ultrasound are a frequency of 5 to 1000 kHz and an output of 10 to 1000 W.
[0292] [Postscript 21]
[0293] The method for manufacturing the composition according to any one of Appendices 18 to 20, wherein the solvent comprises water or an alcohol.
[0294] [Postscript 22]
[0295] The method for manufacturing the composition according to any one of Appendices 18 to 21, wherein the composition (A) further comprises a reducing agent.
[0296] [Postscript 23]
[0297] The method of manufacturing the composition according to any one of Appendices 18 to 22, wherein the composition (A) further comprises a carboxylic acid.
[0298] [Postscript 24]
[0299] The method for manufacturing the composition according to any one of Appendices 18 to 23, wherein the substrate particles are particles selected from Si, W, SiO2, Cr and Mo.
[0300] [Postscript 25]
[0301] The method for manufacturing the composition according to any one of Appendices 18 to 24, wherein the metal compound is an oxide of a metal and / or a carboxylate of a metal.
Claims
1. A composition comprising: Composite particles Organic matter, and Particles containing Ag and / or Cu other than the aforementioned composite particles, The composite particles comprise substrate particles and Ag and / or Cu supported on the substrate particles. The linear expansion coefficient of the substrate particles is below 8 ppm / K. The particle sintering rate of the composition, expressed by the following formula (1), is 30% or more. Particle sintering rate = (Total number of substrate particles with a length of 100 nm or more oriented in at least one direction and bonded to the bonded material in an image obtained by taking a cross-section of the sintered body after the following sintering process at 20,000x magnification using FE-SEM) / (Total number of substrate particles with a length of 100 nm or more oriented in at least one direction in an image obtained by taking a cross-section of the sintered body after the following sintering process at 20,000x magnification using FE-SEM) (1) Sintering process: The composition is printed on a Cu substrate with a 2μm thick Ag coating using a metal mask (5mm opening, 0.15mm mask thickness). The Cu substrate is placed on a heating plate maintained at 100°C for 1 minute, then removed from the heating plate and allowed to return to room temperature. The Cu substrate is then placed on a heating plate maintained at 250°C for 30 minutes, then removed from the heating plate and allowed to return to room temperature.
2. The composition according to claim 1, wherein, The substrate particles are particles selected from Si, W, SiO2, Cr and Mo.
3. The composition according to claim 1 or 2, wherein, Of all the particles contained in the composition, Ag and / or Cu account for 50% to 95% by volume.
4. The composition according to claim 1 or 2, wherein, In images obtained by taking pictures of any five locations in the cross-section of the composite particles using SEM at 1000x magnification, the average number of the following particle aggregates A is less than 2. Particle aggregate A: contains multiple substrate particles, and Ag and / or Cu, wherein the area ratio of the supported Ag and / or Cu is more than 70% relative to the substrate particles, and the diameter of the longest part of the aggregate is more than 5 μm.
5. A method for manufacturing a composition, said composition comprising composite particles on which a metal is supported, and a solvent. The manufacturing method includes: The process of irradiating a composition (A) containing the substrate particles, a metal compound that is a raw material for the metal, and a solvent with ultrasound in order to manufacture the composite particles. The manufacturing method yields a composition with a particle sintering rate of 30% or more, as expressed by the following formula (1). Particle sintering rate = (Total number of substrate particles with a length of 100 nm or more oriented in at least one direction and bonded to the bonded material in an image obtained by taking a cross-section of the sintered body after the following sintering process at 20,000x magnification using FE-SEM) / (Total number of substrate particles with a length of 100 nm or more oriented in at least one direction in an image obtained by taking a cross-section of the sintered body after the following sintering process at 20,000x magnification using FE-SEM) (1) Sintering process: The composition is printed on a Cu substrate with a 2μm thick Ag coating using a metal mask (5mm opening, 0.15mm mask thickness). The Cu substrate is placed on a heating plate maintained at 100°C for 1 minute, then removed from the heating plate and allowed to return to room temperature. The Cu substrate is then placed on a heating plate maintained at 250°C for 30 minutes, then removed from the heating plate and allowed to return to room temperature.
6. The method for manufacturing the composition according to claim 5, wherein, In the process of irradiating ultrasound, the temperature of the composition (A) is 20°C to 100°C.
7. The method for manufacturing the composition according to claim 5 or 6, wherein, In the process of irradiating with ultrasound, the irradiation conditions are a frequency of 5kHz to 1000kHz and an output of 10W to 1000W.
8. The method for manufacturing the composition according to claim 5 or 6, wherein, The solvent contains water or alcohol.
9. A method for manufacturing the composition according to claim 5 or 6, wherein, The composition (A) further comprises a reducing agent.
10. A method for manufacturing the composition according to claim 5 or 6, wherein, The composition (A) further comprises a carboxylic acid.
11. A method for manufacturing the composition according to claim 5 or 6, wherein, The substrate particles are particles selected from Si, W, SiO2, Cr and Mo.
12. The method for manufacturing the composition according to claim 5 or 6, wherein, The metal compound is an oxide of a metal and / or a carboxylate of a metal.
Citation Information
Patent Citations
Metal nanoparticle and method for producing the composite powder
JP2010065265A
LED lighting device and LED lighting instrument
JP2024034444A
Affine linear weighted intra prediction
JP2024157033A
Metallic sintered bonding body and die bonding method
WO2018037992A1